Implementation of An Automated Intelligence Collection Framework Based on Go Language - Zhang, Youming; Chen, Ke (Journal of Artificial Intelligence and Information, 2025)
At present, search engine hacking is still a highly threatening attack method to security. Through search engines, victims' website backend or source code, and even users' personal privacy information can be directly obtained from the network. In order to minimize this security threat as much as possible and improve the efficiency of maintaining network security, an automated intelligence collection framework based on Go language is proposed, mainly through Bing and Google search engines for intelligence collection. This framework utilizes the concurrency feature of Go language, greatly improving the performance of crawlers and accelerating the speed of intelligence collection.